Hydrogels with incorporated graphene oxide as light‐addressable actuator materials for cell culture environments in lab‐on‐chip systems. Issue 6 (18th March 2016) - Breuer, L.; Raue, M.; Strobel, M.; Mang, T.; Schöning, M. J.; Thoelen, R.; Wagner, T.
Abstract: Abstractauthoren Graphene oxide (GO) nanoparticles were incorporated in temperature‐sensitive Poly(N‐isopropylacrylamide) (PNIPAAm) hydrogels. The nanoparticles increase the light absorption and convert light energy into heat efficiently. Thus, the hydrogels with GO can be stimulated spatially resolved by illumination as it was demonstrated by IR thermography. The temporal progression of the temperature maximum was detected for different concentrations of GO within the polymer network. Furthermore, the compatibility of PNIPAAm hydrogels with GO and cell cultures was investigated. For this purpose, culture medium was incubated with hydrogels containing GO and the viability and morphology of chinese hamster ovary (CHO) cells was examined after several days of culturing in presence of this medium.